Competence, Tech Innovation, and Islamic Work Culture: Driving Performance and Its Implications for Quality in Islamic School - Syamsul Bahri; Ansar Amir (ETDC: Indonesian Journal of Research and Educational Review, 2026)
This study examines the influence of competence, technological innovation, and Islamic work culture on educators’ performance and its implications for educational quality in madrasahs. The research employs a quantitative explanatory approach with a survey method. The population consists of Islamic School teachers in Makassar City, including Madrasah Ibtidaiyah, Tsanawiyah, and Aliyah, with a sample of 88 respondents selected using the Slovin formula. Data was collected through questionnaires and analyzed using multiple linear regression and path analysis with SPSS. The structural model analysis shows that competence, technological innovation, and Islamic work culture simultaneously contribute 76.4% to the performance of teaching and education staff, with technological innovation as the most dominant determinant, underscoring the importance of digital adaptation for work efficiency in the modern era. Furthermore, the integration of these three independent variables with performance provides a significant simultaneous contribution of 79.6% to the quality of education, where Islamic work culture emerges as the most dominant factor, confirming that the internalization of spiritual values is the main foundation in realizing quality education services. Through path analysis, performance is proven to play a significant role as a mediating (intervening) variable, indicating that the acceleration of achieving educational quality in madrasahs cannot stand alone but must be realized gradually through optimizing the actual performance of teachers and staff first.